Analisis Variasi Komposisi terhadap Kekuatan Tarik Komposit Serat Daun Nanas dengan Orientasi Random - Evy Agnessylviana Rooseta; Wiwik Dwi Pratiwi; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Pineapple leaf waste that is treated properly will provide added value. For example, the use of pineapple leaf fiber for the manufacture of composites. In addition, composites with natural fibers are lighter than synthetic fibers. Synthetic fibers also have several disadvantages, namely they can irritate the hands and can injure the lungs during the production process. In this study, research was conducted on the effect of orientation and composition on the tensile strength of pineapple leaf fiber reinforced composites. The arrangement of the fibers used is random, while the variations in fiber composition are 55%, 60% and 65% based on volume fraction. Pineapple leaf fiber used through the delignification process using 5% NaOH solution for 2 hours. The composite that produces the greatest tensile strength is a composite with one direction fiber orientation with a fiber composition of 55%, namely 7.18 ± 0.91 MPa. While the lowest tensile strength in random orientation composites with a fiber composition of 65% is 4.04 ± 1.02 MPa.